PENGARUH AUDIT TENURE, FEE AUDIT, REPUTASI AUDITOR DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT - Aini Nur Hasanah; Suhendro; Endang Masitoh (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study investigates the impact of several key factors, including auditor tenure, audit fees, auditor reputation, and auditor rotation, on the quality of audit outcomes. The research utilizes secondary data sourced from the financial statements of non-cyclical consumer goods companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. Employing purposive sampling, 33 companies were selected as the research sample. Data analysis was performed using EViews software, leveraging logistic regression with a probit approach. The findings demonstrate that auditor tenure, auditor reputation, and auditor rotation exert a significant influence on the quality of audits. Conversely, the study provides limited evidence to support a substantial relationship between audit fees and the quality of audit outcomes.